Bilinçli farkındalık özelliğinin, bireylerin sürdürülebilir tüketim davranışına etkisi ve iyi hissetme durumlarıyla ilişkisine bakış - Özkök, Berna (İstanbul Bilgi Üniversitesi, 2022)
ABSTRACT: In this study, consumer behavior is examined in the context of the concept of sustainable marketing. In this framework, individuals' conscious awareness levels (mindfulness) and well-being are examined. In addition, the relationship between self-esteem and sustainable consumption behavior is also examined. The concept of consumption is tried to be explained by referring to the history of consumption starting from the industrial revolution. Then, international conferences and meetings on environment and sustainability are mentioned. The initial aim of the study is to reveal the effect of conscious awareness, well-being and self-esteem on sustainable consumer behavior and the reflection of this behavior on individuals.. Attention is drawn to the importance of sustainable consumption against the ecological problems that arise today. The consumer's personal view of sustainable consumption and how much he internalizes this behavior are taken into account. In this framework, the contributions of sustainable consumption, well-being, mindfulness and self-respect to each other are measured. The concept of selfesteem is measured with the Rosenberg Self-Esteem Scale (RBSS) - Short Form. The concept of wellbeing is measured with the Warwick-Edinburgh Mental WellBeing Scale. The concept of mindfulness is measured by the Mindful Attention Awareness Scale (MAAS). The sub-dimension of the "Sustainable Consumption Behavior" Scale is used for Sustainable Consumption Behavior. Data collection consists of 72 questions survey and 7 questions demographic information. There was a positive relationship between Self-Esteem and Mental Well-Being, but a negative relationship between Self-Esteem and Mindfulness. A weak positive relationship was found between Self-Esteem and Sustainable Consumption Behavior. There was a weak negative relationship between Mental Well-Being and Mindfulness. On the other hand, a low level positive relationship was revealed between Mental Well-Being and Sustainable Consumption. Also there has found no relationship between Mindfulness and Sustainable Consumption Behavior.

ÖZET: Bu çalışmada su?rdu?ru?lebilir pazarlama kavramı bağlamında tu?ketici davranışlarına bakılmaktadır. Bu çercevede bireylerin bilinçli farkındalık du?zeylerine (mindfulness) ve iyi hissetme, iyi olma durumuna (wellbeing) bakılmaktadır. Ayrıca özsaygı ile su?rdu?ru?lebilir tu?ketim davranışı arasındaki ilişki de incelenmektedir. Sanayi devriminden başlayarak tu?ketimin tarihçesine değinilerek tu?ketim kavramı açıklanmaya çalışılmaktadır. Daha sonra çevre ve su?rdu?ru?lebilirlik ile ilgili yapılan uluslarası çalışmalara değinilmektedir. Çalışmanın başlangıç amacı, bilinçli farkındalığın, iyi olma halinin ve özsaygının su?rdu?ru?lebilir tu?ketici davranışının u?zerindeki etkisini ve bu davranışın bireylere yansımasını ortaya çıkarmaktır. Gu?nu?mu?zde çıkan ekolojik sorunlara karşı su?rdu?ru?lebilir tu?ketimin önemine dikkat çekilmektedir. Tu?keticinin kişisel gözu?nden su?rdu?ru?lebilir tu?ketime bakışı ve bu davranışı ne kadar içsellestirdiği göz önu?ne konulmaktadır. Tu?m bu çercevede su?rdu?ru?lebilir tu?ketimin, iyi olma halinin, bilinçli farkındalığın ve özsaygının birbirlerine olan katkıları ölçu?lmektedir. Özsaygı kavramı Rosenberg Benlik Saygısı Ölçeği (RBSÖ) - Kısa Formu ile ölçu?lmektedir. Wellbeing kavramı ise Warwick-Edinburgh Mental İyi Oluş Ölçeği ile ölçu?lmektedir. Mindfulness kavramı Bilinçli Farkındalık Ölçeği-BFÖ (The Mindful Attention Awareness Scale-MAAS) ile ölçu?lmektedir. Su?rdu?ru?lebilir Tu?ketim Davranışı için “Su?rdu?ru?lebilir Tu?ketim Davranışı” Ölçeği’nin alt boyutu kullanılmaktadır. Veri toplama, 72 sorulu anket ve 7 sorulu demografik bilgiler içermektedir. Benlik Saygısı ile Mental İyi Oluş arasında pozitif yönde, fakat Benlik Saygısı ile Bilinçli Farkındalık arasında negatif yönde bir ilişki ortaya çıkmıştır. Benlik Saygısı ile Su?rdu?ru?lebilir Tu?ketim Davranışı arasında ise pozitif yönde zayıf bir ilişki ortaya konmuştur. Mental İyi Oluş ile Bilinçli Farkındalık arasında ise negatif yönde zayıf bir ilişki çıkmıştır. Mental İyi Oluş ile Su?rdu?ru?lebilir Tu?ketim arasında ise du?şu?k olsa da pozitif yönde bir ilişki ortaya konmuştur. Bilinçli Farkındalık ile Su?rdu?ru?lebilir Tu?ketim Davranışı arasında ise bir ilişki gözu?kmemektedir.
The effect of mindfulness on sustainable consumption behavior of ındividuals and its relationship with wellbeing
Keywords: Su?rdu?ru?lebilir Tu?ketim; İyi Oluş; Su?rdu?ru?lebilir Tu?ketim Davranışı; Bilinçli Farkındalık; Özsaygı; Sustainable Consumption; sustainable consumer behavior; Wellbeing; Mindfulness; Self-Respect